2022
DOI: 10.3390/plants11050697
|View full text |Cite
|
Sign up to set email alerts
|

Pulp Mineral Content of Passion Fruit Germplasm Grown in Ecuador and Its Relationship with Fruit Quality Traits

Abstract: There are several species of passion fruit grown in South America. However, there is a lack of information about the mineral content in their pulp. Thus, the objective of the present research was to determine the mineral content in the pulp of different germplasms of passion fruit [Passiflora edulis f. flavicarpa (INIAP 2009 and P10), P. alata (Sweet passion fruit), P. edulis f. edulis (Gulupa) and Passiflora sp. (Criollo POR1 and Criollo PICH1)] grown in Ecuador and to determine their relationship with releva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 57 publications
(79 reference statements)
0
1
0
Order By: Relevance
“…It has been reported that some germplasm of yellow passion fruit (i.e. INIAP 2009) can reach up to twice the peel thickness of purple passion fruit (Viera et al, 2022a); however, these authors did not find statistical differences for this trait between 'POR1' and 'Gulupa' grown in open field. In this study, 'POR1' showed higher peel thickness than the value (5.87 mm) reported by the latter authors but it has been reported that this trait might be varied due to a genotype × environment effect (Viera et al, 2020).…”
Section: Discussionmentioning
confidence: 79%
“…It has been reported that some germplasm of yellow passion fruit (i.e. INIAP 2009) can reach up to twice the peel thickness of purple passion fruit (Viera et al, 2022a); however, these authors did not find statistical differences for this trait between 'POR1' and 'Gulupa' grown in open field. In this study, 'POR1' showed higher peel thickness than the value (5.87 mm) reported by the latter authors but it has been reported that this trait might be varied due to a genotype × environment effect (Viera et al, 2020).…”
Section: Discussionmentioning
confidence: 79%